Wittgenstein and the genesis of neo-pragmatism in American thought. Issue 1 (2nd January 2016) - Hmiel, John Erik
SUMMARY: While commentators have noted that the revival of pragmatism in recent decades can be understood in the context of a larger turn towards anti-foundational thought, they have largely ignored the important and complicated role that Ludwig Wittgenstein's ideas about foundationalism played in that revival. By tracing Wittgenstein's influence on the philosophers Stanley Cavell and Thomas Kuhn, the author first suggests that the revival of neo-pragmatism is better understood in the context of mid-century analytic philosophy they inherited, as well as Wittgenstein's unique contribution and challenge to that tradition. Next, by showing how the Wittgensteinian ideas of Cavell and Kuhn played an important role in the decades-long debate between Richard Rorty and Hilary Putnam, arguably the most important catalyst of neo-pragmatist thought, the author shows that Wittgenstein's reframing of Kantian epistemology places the emergence of neo-pragmatism in a larger context of Enlightenment thought in the United States, rather than making it an easy ally of anti-foundational post-structuralism.